Composite organic improving agent as well as preparation method and application thereof
Through the self-assembly heterogeneous nucleation technology of the composite organic improver, mutant spherulites are formed, which solves the turbidity and mechanical property improvement problems of ethylene polymers, and achieves efficient and low-cost ethylene polymer improvement effects, which is suitable for the crystallization and mechanical property improvement of ethylene polymers.
Patent Information
- Application Number
- CN202510711437.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-29
- Publication Date
- 2025-09-05
AI Technical Summary
Existing ethylene polymer additives are difficult to effectively reduce turbidity, improve crystallization properties and mechanical properties, and there are problems with thermal stability. There are few commercial products and they cannot meet the market demand for high strength, high modulus, high transparency and high speed.
A composite organic improver composed of monooxalyl diamide and bisoxalyl diamide derivatives is used to induce the ethylene polymer molecular chain to form mutant spherulites through self-assembly heterogeneous nucleation. The mutant spherulites have a central bright area and an extinction dark area. The compound ratio and substitution group structure are optimized to improve the nucleation efficiency and thermal stability.
It significantly reduces the turbidity of ethylene polymers, increases the peak crystallization temperature, shortens the half-crystallization time, improves mechanical properties, and avoids yellowing and precipitation during high-temperature processing. It is low-cost and easy to industrialize.
Smart Images

Figure CN120590685A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a composite organic improver and a preparation method and application thereof. Background Art
[0002] Ethylene polymers are very popular semi-crystalline polymer materials, not only with the largest consumption but also with a wide range of applications. Despite this, ethylene polymers still struggle to meet market demands for high strength, high modulus, high transparency, and high speed. Additives are a common method for improving the crystallization and macroscopic properties of semi-crystalline polymers. However, to date, additives for ethylene polymers, particularly commercial additive products, are rare. Therefore, it is necessary to develop a novel, highly effective additive to improve the crystallization, turbidity, and mechanical properties of ethylene polymers to broaden their applications.
[0003] Turbidity is a commonly used measure of the clarity of polymer products, expressed as a percentage, with or without additives. Generally, even a single-percentage-point reduction in turbidity is of significant industrial significance. Given the demanding R&D landscape of ethylene polymers, even a single-percentage-point reduction, even a fractional-percentage-point reduction, is invaluable in the field. It's important to note that not all compounds can reduce turbidity. Of the 118 million compounds currently available, fewer than 10 are known to reduce polymer turbidity. A further limitation is that even inappropriate additive dosage can result in turbidity remaining unchanged or even increasing. Therefore, the plastics additive industry is constantly searching for additives that can provide lower turbidity and at lower dosage levels. However, low turbidity isn't the only factor in determining the suitability of a plastics additive. Poor thermal stability can lead to undesirable yellowing and precipitation at high processing temperatures, necessitating additives with excellent thermal stability.
[0004] The types and quantities of organic improvers for ethylene polymers are relatively limited. This is primarily due to the regular molecular chain structure of ethylene polymers, resulting in the fastest crystallization rate of all polymers. Therefore, organic improvers for ethylene polymers must possess higher nucleation efficiency and capacity. Consequently, the research and development requirements for organic improvers for ethylene polymers are among the most demanding of all polymers. Currently, there are very few commercially available products that claim to be organic improvers for ethylene polymers, and few, if any, combine the functions of promoting crystallization, increasing clarity, and enhancing mechanical properties. HPN-20E is one of the few commercially available ethylene polymer additives, primarily used to improve the airtightness of finished products with little to no reduction in turbidity. Millad 3988 is a classic additive used to improve polypropylene turbidity, with over 30 years of commercial application. Although it improves ethylene polymer turbidity better than HPN-20E, the improvement is still subpar and has not been put into practical use.
[0005] Spherulites are the most common crystalline form of polymers, including ethylene polymers. Spherulites appear as a characteristic black cross extinction image between crossed polarizers in a polarizing microscope. The properties of semicrystalline polymers are generally determined by their crystal structure, such as spherulite. During the initial stages of spherulite growth, a process called nucleation must occur, followed by chain folding or self-organization of the lamellae around this nucleus. In homogeneous nucleation, nucleation occurs at defects or inconsistencies within the polymer chain. In heterogeneous nucleation, nucleation occurs on the surface of an external phase, known as an additive, nucleation promoter, or organic modifier. Generally, in polymers with heterogeneous nucleation, crystallization occurs earlier and faster during cooling, shortening cooling time, increasing nucleation density, and reducing spherulite size. Existing additives designed to increase nucleation density and reduce spherulite size have limitations in ethylene polymers, as evidenced by a turbidity reduction typically below 15%, without the ability to simultaneously improve mechanical and crystallization properties. Furthermore, in the prior art, in the presence of additives, the increase in the nucleation efficiency of ethylene polymers, the reduction in half-crystallization time, the reduction in product turbidity, and the improvement in mechanical properties are limited or incompatible, and need to be further improved.
[0006] In summary, the object of the present invention is to at least partially overcome the shortcomings of the prior art and provide a composite organic improver for ethylene polymers that has low dosage, low cost, no yellowing and precipitation, promotes nucleation and crystallization, shortens the molding cycle, and improves turbidity and mechanical properties. In addition, a preparation method and application of the composite organic improver with a short process, low cost, less raw materials, and high yield are provided. Summary of the Invention
[0007] The technical problem to be solved by the present invention is to overcome the shortcomings of the existing technology and provide a composite organic improver that can improve turbidity, accelerate crystallization and enhance mechanical properties. Correspondingly, a variety of preparation methods of the composite organic improver with short processes, low costs, less raw materials and high yields are provided, and the application of the composite organic improver is provided.
[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions.
[0009] A composite organic improver, comprising compound A and compound B, wherein compound A is one or more monooxalyl diamide derivatives, and compound B is one or more bisoxalyl diamide derivatives, wherein compound A and compound B can induce ethylene polymer molecular chains to form variant spherulites through self-assembly heterogeneous nucleation, wherein the variant spherulites include a central bright region and an extinction dark region, wherein the extinction dark region surrounds the central bright region;
[0010] The structural formula of the monooxalyl diamide derivative is shown in formula (I):
[0011]
[0012] The structural formula of the bisoxalyl diamide derivative is shown in formula (II):
[0013]
[0014] R1, R2, R3, and R5 are independently one of a hydrocarbon group having 1 to 40 carbon atoms and a hydrocarbon group substituted with a hydroxyl group having 1 to 40 carbon atoms, and R4 is one of a hydrocarbon group having 1 to 40 carbon atoms.
[0015] The above-mentioned composite organic improver preferably has one or more of the following characteristics:
[0016] (1) The difference ΔW between the peak positions of the characteristic absorption peaks of the NH bending and CN stretching coupling vibrations between the compound A and the compound B in the infrared spectrum within the range of 1600 to 1400 wavenumbers does not exceed 15 wavenumbers;
[0017] (2) The composite organic improver has a characteristic absorption peak of NH stretching vibration in the wave number range of 3500-3100 in the infrared spectrum, and a characteristic absorption peak of carbonyl stretching vibration in the wave number range of 1700-1600;
[0018] (3) The melting point range of the composite organic improver is 100°C to 370°C;
[0019] (4) the composite organic improver is heated from 25° C. to a molten state and then cooled to 25° C. to form a fibrous structure;
[0020] (5) The composite organic improver is characterized by two-stage thermal weight loss in the first-stage thermal weight loss temperature range of 100°C to 300°C and the second-stage thermal weight loss temperature range of 200°C to 450°C under thermogravimetric analysis, or multiple-stage thermal weight loss in the thermal weight loss temperature range of 100°C to 450°C.
[0021] The composite organic improver described above is more preferably characterized in that, in feature (1), the difference ΔW between the peak positions of the NH bending and CN stretching coupled vibration characteristic absorption peaks existing in the infrared spectrum within the range of 1600 to 1400 wavenumbers between the compound A and the compound B does not exceed 10 wavenumbers;
[0022] And / or, in feature (3), the melting point range of the composite organic improver is 200°C to 320°C.
[0023] The above-mentioned composite organic improver is more preferably characterized in that, in feature (1), the difference ΔW between the peak positions of the characteristic absorption peaks of NH bending and CN stretching coupling vibrations existing in the infrared spectrum within the range of 1600 to 1400 wavenumbers between the compound A and the compound B does not exceed 5 wavenumbers;
[0024] And / or, in feature (3), the melting point range of the composite organic improver is 250°C to 300°C.
[0025] In the above-mentioned composite organic improver, preferably, the mass ratio of the compound A to the compound B is 1-1000:1-1000.
[0026] More preferably, the mass ratio of the compound A to the compound B in the composite organic improver is 1-100:1-100.
[0027] In the above-mentioned composite organic improver, preferably, the variant spherulites have one or more of the following characteristics:
[0028] (1) The overall morphology of the variant spherulites is spherical or quasi-spherical;
[0029] (2) The maximum diameter of the modified spherulites is 20 μm to 500 μm, more preferably 20 μm to 300 μm;
[0030] (3) the central bright area is composed of one or more (i.e., one or more) needle-shaped units, narrow dumbbell-shaped units, or bundle-shaped units;
[0031] (4) The central bright area is radial in shape as a whole;
[0032] (5) The shape of the dark area includes one or more of a double semicircle, an oval, a circle, a jujube-shaped circle, and an oblate circle;
[0033] (6) The area of the extinction dark zone accounts for 50% to 95% of the total area of the mutant spherulites.
[0034] The above-mentioned composite organic improver, preferably, said R1, R2, R3, R5 are independently selected from methyl, ethyl, propyl, butyl, isobutyl, pentyl, hexyl, heptyl, octyl, 2-ethylhexyl, nonyl, decyl, undecyl, dodecyl, tetradecyl, hexadecyl, octadecyl, cyclohexylmethyl 1-Cyclohexylethyl 2-Cyclohexylethyl One or more of cyclohexyl, phenyl, benzyl, 4-methylbenzyl, 2-methylallyl, 2-hydroxyethyl, 3-hydroxypropyl, 2-hydroxybutyl, 4-hydroxybutyl, 5-hydroxypentyl, 6-hydroxyhexyl, 10-hydroxydecyl, 11-hydroxyundecyl and 12-hydroxydodecyl;
[0035] The R4 is selected from ethanediyl, propanediyl (including propane-1,2-diyl propane-1,3-diyl), butanediyl, pentanediyl, 2,2-dimethylpropane-1,3-diyl Hexanediyl, heptanediyl, octanediyl, decanediyl, dodecanediyl, cyclohexanediyl (including cyclohexane-1,2-diyl, cyclohexane-1,3-diyl, cyclohexane-1,4-diyl), methylbenzenediyl (including 4-methylbenzene-1,3-diyl 2-methylbenzene-1,4-diyl), dimethylbenzene-1,4-diyl (including 2,5-dimethylbenzene-1,4-diyl ), benzene diyl (including benzene-1,4-diyl, benzene-1,3-diyl), naphthalene diyl (including naphthalene-1,2-diyl, naphthalene-1,3-diyl, naphthalene-1,4-diyl, naphthalene-1,5-diyl, naphthalene-1,7-diyl, naphthalene-1,8-diyl, naphthalene-2,3-diyl, naphthalene-2,6-diyl, naphthalene-2,7-diyl), biphenyl diyl (including biphenyl-2,2'-diyl, biphenyl-4,4'-diyl), dimethyl biphenyl (including 3,3'-dimethyl biphenyl-4,4'-diyl ), diphenylmethanediyl (including diphenylmethane-4,4'-diyl ), (1-methylethylidene)biphenyl-4,4'-diyl and 1,3,3-trimethylcyclohexyl-5-yl That is, more preferably, the R4 is selected from ethanediyl, propane-1,2-diyl, propane-1,3-diyl, butanediyl, pentanediyl, 2,2-dimethylpropane-1,3-diyl, hexanediyl, heptanediyl, octanediyl, decanediyl, dodecanediyl, cyclohexane-1,2-diyl, cyclohexane-1,3-diyl, cyclohexane-1,4-diyl, 4-methylbenzene-1,3-diyl, 2-methylbenzene-1,4-diyl, 2,5-dimethylbenzene-1,4-diyl, benzene-1,3-diyl, benzene-1,4-diyl, benzene-1,3-diyl, cyclohexane-1,2-diyl, cyclohexane-1,3-diyl, cyclohexane-1,4-diyl, 4-methylbenzene-1,3-diyl, 2-methylbenzene-1,4-diyl, 2,5-dimethylbenzene-1,4-diyl, benzene-1,3-diyl, cyclohexane-1,4-diyl, cyclohexane ... One or more of diphenylmethane, 1,2-diyl, 1,3-diyl, 1,4-diyl, 1,5-diyl, 1,7-diyl, 1,8-diyl, 2,3-diyl, 2,6-diyl, 2,7-diyl, biphenyl-2,2'-diyl, biphenyl-4,4'-diyl, 3,3'-dimethylbiphenyl-4,4'-diyl, diphenylmethane-4,4'-diyl, (1-methylethylidene)biphenyl-4,4'-diyl and 1,3,3-trimethylcyclohexylmethyl-5-yl.
[0036] As a general technical concept, the present invention also provides a method for preparing the above-mentioned composite organic improver, which is recorded as method 1 and comprises the following steps:
[0037] S1, adding oxalic acid diester to a reaction vessel, then adding diamine, and reacting at 0° C. to 40° C. to obtain a first reaction mixture;
[0038] S2, adding solvent B to the first reaction mixture, heating until dissolved, then adding a monoamine, and performing a reflux reaction, wherein the monoamine is a hydrocarbon monoamine and / or an alcohol hydrocarbon monoamine, and is purified and separated to obtain a composite organic improver;
[0039] The molar ratio of the oxalic acid diester, the diamine and the monoamine is m:1:(2m+n-2), 2.5≤m≤1000, and 0≤n≤10.
[0040] The preparation method of the composite organic improver mentioned above, preferably, the preparation method (method 1) has one or more of the following characteristics (1) to (9):
[0041] (1) In step S1, the oxalic acid diester includes one or more of dimethyl oxalate, diethyl oxalate, dipropyl oxalate, dibutyl oxalate and dioctyl oxalate;
[0042] (2) In step S1, the diamine includes one or more of ethylenediamine, propylenediamine, butylenediamine, pentamethylenediamine, dimethylpropylenediamine, hexamethylenediamine, heptamethylenediamine, octanediamine, decanediamine, dodecanediamine, cyclohexanediamine, methylphenylenediamine, dimethylphenylenediamine, phenylenediamine, naphthalenediamine, benzyldiamine, dimethylbenzidine, 4,4'-diaminodiphenylmethane, 4,4'-(1-methylethylidene)dianiline, and 5-amino-1,3,3-trimethylcyclohexylamine;
[0043] (3) In step S1, the diamine is first mixed with solvent A and then added to the reaction vessel, wherein the solvent A comprises one or more of a halogenated hydrocarbon having 1 to 5 carbon atoms, an alcohol having 1 to 40 carbon atoms, an amide having 1 to 6 carbon atoms, an N-substituted amide having 1 to 6 carbon atoms, and tetrahydrofuran;
[0044] (4) In step S2, the hydrocarbon monoamine includes one or more of methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, heptylamine, octylamine, 2-ethylhexylamine, nonylamine, decylamine, undecylamine, dodecylamine, tetradecylamine, hexadecylamine, octadecylamine, behenyl primary amine, cyclohexylamine, cyclohexylmethylamine, 1-cyclohexylethylamine, 2-cyclohexylethylamine, aniline, benzylamine, 4-methylbenzylamine, and 2-methylallylamine;
[0045] (5) In step S2, the alcohol-alkyl monoamine includes one or more of ethanolamine, propanolamine, 2-hydroxybutylamine, 4-hydroxybutylamine, 5-hydroxypentylamine, hexanolamine, hexanolamine, undecanolamine and dodecanolamine;
[0046] (6) In step S2, the solvent B includes one or more of a halogenated hydrocarbon having 1 to 5 carbon atoms, an alcohol having 1 to 40 carbon atoms, an amide having 1 to 6 carbon atoms, an N-substituted amide having 1 to 6 carbon atoms, and tetrahydrofuran;
[0047] (7) In step S2, the monoamine is first mixed with solvent E, which is the same as solvent B, and then added to the reaction vessel;
[0048] (8) In step S2, the purification includes filtering, washing, and drying;
[0049] (9) The diamine and the monoamine are added to the reaction vessel in the form of dropwise addition, flow addition or batch addition.
[0050] As a general technical concept, the present invention also provides a method for preparing the above-mentioned composite organic improver, which is recorded as method 2 and comprises the following steps:
[0051] S1. Adding an oxalic acid diester and a monoamine into a reaction vessel and reacting at 0° C. to 85° C. to obtain a reaction intermediate, wherein the monoamine is a hydrocarbon monoamine and / or an alcohol hydrocarbon monoamine;
[0052] S2, adding solvent D to the reaction intermediate, heating until dissolved, then adding diamine to carry out reflux reaction, and refining and separating after the reaction to obtain a composite organic improver;
[0053] The molar ratio of the oxalic acid diester, the monoamine and the diamine is 1:p:(1-0.5p), and 1<p<2.
[0054] The preparation method of the composite organic improver mentioned above, preferably, the preparation method (method 2) has one or more of the following characteristics (1) to (8):
[0055] (1) In step S1, the oxalic acid diester includes one or more of dimethyl oxalate, diethyl oxalate, dipropyl oxalate, dibutyl oxalate and dioctyl oxalate;
[0056] (2) In step S1, the hydrocarbon monoamine includes one or more of methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, heptylamine, octylamine, 2-ethylhexylamine, nonylamine, decylamine, undecylamine, dodecylamine, tetradecylamine, hexadecylamine, octadecylamine, behenyl primary amine, cyclohexylamine, cyclohexylmethylamine, 1-cyclohexylethylamine, 2-cyclohexylethylamine, aniline, benzylamine, 4-methylbenzylamine, and 2-methylallylamine;
[0057] (3) In step S1, the alcohol-alkyl monoamine includes one or more of ethanolamine, propanolamine, 2-hydroxybutylamine, 4-hydroxybutylamine, 5-hydroxypentylamine, hexanolamine, hexanolamine, undecanolamine and dodecanolamine;
[0058] (4) In step S1, the monoamine is first mixed with a solvent C and then added to the reaction vessel, wherein the solvent C comprises one or more of a halogenated hydrocarbon having 1 to 5 carbon atoms, an alcohol having 1 to 40 carbon atoms, an amide having 1 to 6 carbon atoms, an N-substituted amide having 1 to 6 carbon atoms, tetrahydrofuran, acetonitrile, and an aromatic hydrocarbon;
[0059] (5) In step S2, the diamine includes one or more of ethylenediamine, propylenediamine, butylenediamine, pentamethylenediamine, dimethylpropylenediamine, hexamethylenediamine, heptamethylenediamine, octanediamine, decanediamine, dodecanediamine, cyclohexanediamine, methylphenylenediamine, dimethylphenylenediamine, phenylenediamine, naphthalenediamine, benzyldiamine, dimethylbenzidine, 4,4'-diaminodiphenylmethane, 4,4'-(1-methylethylidene)dianiline, and 5-amino-1,3,3-trimethylcyclohexylamine;
[0060] (6) In step S2, the solvent D includes one or more of a halogenated hydrocarbon having 1 to 5 carbon atoms, an alcohol having 1 to 40 carbon atoms, an amide having 1 to 6 carbon atoms, an N-substituted amide having 1 to 6 carbon atoms, tetrahydrofuran, acetonitrile, and an aromatic hydrocarbon;
[0061] (7) In step S2, the diamine is first mixed with solvent F, which is the same as solvent D, and then added to the reaction vessel;
[0062] (8) The refining includes filtering, washing, and drying;
[0063] (9) The monoamine and the diamine are added to the reaction vessel in the form of dropwise addition, flow addition or batch addition.
[0064] As a general technical concept, the present invention also provides a use of the above-mentioned composite organic improver or the composite organic improver prepared by the above-mentioned preparation method as a polymer additive.
[0065] In the above application, preferably, the polymer is an ethylene polymer.
[0066] In the present invention, the composite organic improver appears in the form of a white powder, white lumps, light yellow powder, or light yellow lumps. The modified spherulites described herein are spherical or quasi-spherical crystals that, under a polarizing microscope, exhibit a central bright region surrounded by a surrounding extinct dark region, with a size of no less than 20 microns. The composition, morphology, and size of these modified spherulites differ from typical black cross extinct spherulites. Under a polarizing microscope, the bright region of the modified spherulites of the present invention is composed of one or more needle-like units, narrow dumbbell-shaped units, or bundles of units, forming a radial central structure. The extinct dark region, as seen under a polarizing microscope, exhibits a surrounding structure that is shaped like a double semicircle, oval, circular, oblate, or rounded, for example. The dark region of this extinct structure is significantly larger than the bright region, with the area surrounding the extinct dark region accounting for 50% to 95% of the total area of the modified spherulite. Under a polarizing microscope, the formation of the extinct dark region is due to its minimal effect on the deflection of incident light. In other words, light passing through the extinct dark region is barely deflected, or the deflection angle is small, such as less than 2.5°. A concrete example is glass, which appears entirely dark under a polarizing microscope. Therefore, the heterogeneous nucleation-induced formation of modified spherulites within the macromolecular chains of ethylene polymers by the composite organic modifier of the present invention results in a macroscopic reduction in the turbidity of the ethylene polymer. These modified spherulites are directly related to the clarity of the material.
[0067] In method 1 of the present invention, step S1 is to add 1 mol of diamine to a reaction vessel to react with an excess of m mol of oxalic acid diester, wherein m is preferably any value satisfying 2.5≤m≤1000 (preferably 2.5≤m≤100), and the reaction process is as follows:
[0068]
[0069] In formula (III), the substituent groups R4 and R6 are independently selected from hydrocarbon groups of 1 to 40 carbon atoms, and R6 is a substituent of the oxalic acid diester;
[0070] In step S2, the remaining oxalic acid diester (compound 2) and compound 3 are reacted with 2m+n-2 moles of hydrocarbon monoamine and / or alcohol hydrocarbon monoamine, wherein 2.5≤m≤1000, 0≤n≤10, and n is an excess value. The reaction process is as follows:
[0071]
[0072] The substituent group R1 is independently selected from a hydrocarbon group having 1 to 40 carbon atoms and a hydrocarbon group substituted with a hydroxyl group having 1 to 40 carbon atoms.
[0073] In method 2 of the present invention, step S1 is to add p moles of a monoamine into a reaction vessel and react with 1 mole of an oxalic acid diester at 0° C. to 85° C., wherein p satisfies the condition 1<p<2, and the monoamine is a hydrocarbon monoamine and / or an alcohol hydrocarbon monoamine, and the reaction process is as follows:
[0074]
[0075] wherein the substituent group R1 is one of a hydrocarbon group of 1 to 40 carbon atoms and a hydrocarbon group substituted with a hydroxyl group of 1 to 40 carbon atoms, and R6 is selected from a hydrocarbon group of 1 to 40 carbon atoms;
[0076] In step S2, solvent D is added to the reaction intermediate, heated until dissolved, and then (1-0.5p) mole of diamine is added to carry out reflux reaction. The reaction process is as follows:
[0077]
[0078] The substituent R4 is a hydrocarbon group having 1 to 40 carbon atoms.
[0079] Compared with the prior art, the advantages of the present invention are:
[0080] (1) The composite organic improver of the present invention is a combination of compound A and compound B, wherein compound A is one or more monooxalyl diamine derivatives, and compound B is one or more bisoxalyl diamine derivatives, and the substituent groups are hydrocarbon groups or hydroxyl-substituted hydrocarbon groups, which are similar to the chemical structure of the polymer resin, can be dissolved in the melt at high temperature, have good compatibility, and are evenly dispersed. The composite organic improver of the present invention can control the strength of the intermolecular hydrogen bond on a larger scale by adjusting not only the structure of the substituent groups of the two compounds but also the ratio of the two. The composite organic improver of the present invention can induce the ethylene polymer molecular chain to form a variant spherulite through self-assembly heterogeneous nucleation, and the variant spherulite includes a central bright area and an extinction dark area, and the extinction dark area surrounds the central bright area.
[0081] In the present invention, the central bright area of the variant spherulite is composed of one or more needle-shaped units, narrow dumbbell-shaped units, or bundle-shaped units, and the whole is radial. The extinction dark area is not a conventional black cross extinction image, but presents a double semicircular, oval, circular, jujube-shaped, oblate, etc. shape, and the extinction dark area accounts for a large proportion, with the area of the extinction dark area accounting for 50% to 95% of the total area of the variant spherulite. This variant spherulite is not only directly related to the clarity of the material, but also reflects the good compatibility of the additive with the ethylene polymer. The composite organic improver is used as an additive for the ethylene polymer. The composite organic improver has a low heterogeneous crystal nucleus density and a large size of the variant spherulites, with a maximum diameter of ≥20 microns. The large-sized variant spherulites are more conducive to improving its turbidity, which significantly reduces the turbidity of the ethylene polymer composition, significantly increases the crystallization peak temperature, significantly shortens the half-crystallization time, and significantly improves the mechanical properties.
[0082] (2) In the present invention, the difference ΔW between the peak positions of the characteristic absorption peaks of NH bending and CN stretching coupling vibrations existing in the infrared spectrum range of 1600 to 1400 wavenumbers of compound A and compound B does not exceed 15 wavenumbers, which significantly improves the matching rate between the two compounds. The prepared composite organic improver is beneficial as an additive to obtain an ethylene polymer composition with lower turbidity, higher crystallization temperature, shorter half-crystallization time and better mechanical properties.
[0083] (3) The composite organic improver of the present invention has excellent thermal stability and can reduce the yellowing and precipitation problems of polymers at processing temperatures above 150°C. It also has the advantages of good effect, small dosage and low cost.
[0084] (4) The preparation methods of the composite organic improver of the present invention are all one-pot synthesis methods. There is no direct product of the composite organic improver in the prior art. The method of the present invention directly obtains the target product from relatively simple and easily available raw materials without leaving the pot in the middle, thus avoiding multiple purification steps, saving costs and process time, simplifying the production process, improving efficiency and operational safety, and minimizing the generation of chemical waste and by-products. It is expected to produce good economic benefits, and is environmentally friendly and in line with the principles of green chemistry.
[0085] Method 1 of the present invention adopts a one-pot process, which avoids the loss of the intermediate product Compound 3 during purification, preserves the actual yield of Compound 3, and completely reacts the key raw materials when discharged from the pot, the chemical structure of the final product is stable, and it is easy to purify and separate, which is not likely to cause loss of purification time. This ensures that the yield of the one-pot process is above 90%, which is generally higher than the total yield of less than 50% of the two-pot process. Method 1 has readily available raw materials, low cost, and is easy to industrialize.
[0086] The reaction involved in method 2 of the present invention occurs between a bifunctional raw material and a monofunctional raw material, resulting in fewer by-products and one less starting raw material (acid-binding agent) than in the prior art. The one-pot method employed ensures that key raw materials react completely upon exiting the process, resulting in a stable chemical structure of the final product, which is easily purified and separated without causing significant loss of refining time. This ensures a yield of over 90% for method 2, generally higher than that of the two-pot method. Method 2 also features readily available raw materials, low cost, and ease of industrialization.
[0087] (5) In the present invention, the composite organic improver as an additive provides a new solution for improving the performance of ethylene polymers, brings significant use value, and can meet unmet needs in the market. BRIEF DESCRIPTION OF THE DRAWINGS
[0088] Figure 1 These are infrared spectra of EX1-1 of Example 1 of the present invention, EX4 of Example 7 of the present invention, and CT1 of Comparative Example 1.
[0089] Figure 2 This is a graph showing the effects of different ratios of mono- and bis-oxalyl diamide compounds on the infrared spectrum of the composite organic improver in Example 1 of the present invention, Example 2 of the present invention, Comparative Example 1, and Comparative Example 2.
[0090] Figure 3 This is a polarizing microscope photograph of the ethylene copolymer of Example 4 of the present invention and the composition M1 of EX1-1.
[0091] Figure 4 This is a polarizing microscope photograph of the ethylene copolymer of Example 6 of the present invention and the EX3-1 composition M3.
[0092] Figure 5This is a polarizing microscope photograph of the pure ethylene copolymer O1 of comparative example 5, and the inset is a partial magnified view.
[0093] Figure 6 This is a polarizing microscope photograph of the ethylene copolymer of comparative example 6 and the CT1 composition O2.
[0094] Figure 7 This is a polarizing microscope photograph of the ethylene copolymer of comparative example 7 and the CT2 composition O3.
[0095] Figure 8 It is the characteristic absorption peak of NH bending and CN stretching coupled vibration of the composite organic improver and its components (EX1-1, EX4, CT1, CT2, CT5) in the infrared spectrum range of 1600 to 1400 wavenumbers (displayed as 1580 to 1470 wavenumbers).
[0096] Figure 9 This is a diagram of the fibrous structure of the composite organic improver EX4 according to Example 7 of the present invention observed under a microscope after heat treatment (heating from 25°C to melt and then cooling to 25°C).
[0097] Figure 10 (a) A polarizing microscope photograph of the target sample M4 of the composition of ethylene copolymer and EX4 according to Example 8 of the present invention before etching, and (b) A scanning electron microscope photograph after etching.
[0098] Figure 11 This is a polarizing microscope photograph of the ethylene copolymer of Example 11 of the present invention and the EX5 composition M5.
[0099] Figure 12 This is a polarizing microscope photograph of the composition M6 of the ethylene copolymer of Example 12 of the present invention and EX6. The inset is a partial magnified view. DETAILED DESCRIPTION
[0100] The present invention is further described below with reference to the accompanying drawings and specific preferred embodiments, but the scope of protection of the present invention is not limited thereby. The materials and instruments used in the following examples are all commercially available. The reactor is a conventional reactor equipped with a stirrer, a thermometer, a heating device, a dropping device, and a condenser, but is not limited thereto, as long as the reaction can be carried out.
[0101] In the present invention, the term "one-pot method" refers to the continuous execution of multiple chemical reaction steps in one pot to construct a complex molecular structure without separating and purifying the intermediate products. It is an efficient chemical synthesis strategy.
[0102] In the present invention, the term "ethylene polymer" includes one or more of ethylene homopolymers and ethylene copolymers, more preferably high density polyethylene (density 0.941-0.965 g / cm3 ), medium density polyethylene, low density polyethylene (0.910-0.925g / cm 3 ), linear low density polyethylene, ultra low density polyethylene (density less than 0.910g / cm 3 ), one or more of ultra-high molecular weight polyethylene, metallocene polyethylene, cross-linked polyethylene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ethylene-butene copolymer, ethylene-octene copolymer and cycloolefin copolymer.
[0103] In the present invention, the terms "additive" and "organic improver" can be used interchangeably.
[0104] In the present invention, the term "turbidity" is the percentage of the transmitted light intensity that deviates from the incident light by more than 2.5° to the total transmitted light intensity, also known as "haze." Lower turbidity means better gloss, clarity, and imaging quality of the material.
[0105] In the present invention, the term "polarizing microscope" is a microscope used to study clarified and unclear anisotropic materials. Its basic structure is to add a polarizing plate above and below the sample stage, and the vibration directions of the two polarizing plates are placed at right angles to each other.
[0106] In the present invention, the term "extinction dark area ratio" refers to the ratio of the extinction dark area to the total area of the variant spherulite under a polarizing microscope. The extinction dark area and the area of the variant spherulite are estimated by counting the corresponding areas in the polarizing microscope photograph using computer software.
[0107] In this invention, the term "etching" refers to a method of treating samples for electron microscopy observation using an etchant that damages the crystalline and amorphous regions of a semi-crystalline polymer sample to varying degrees, preferentially destroying the loosely packed amorphous regions, thereby more clearly revealing the texture of the crystalline regions. This technique enables clearer observation of the internal structural details of the polymer and the effects of additives on the crystalline regions. The etchant in this invention consists of a strong oxidant and an acid.
[0108] In the present invention, the term "half-crystallization time" refers to the time it takes for a polymer to undergo half of its isothermal crystallization process at a certain temperature. It is a quantitative indicator that describes the crystallization speed and efficiency.
[0109] Example 1
[0110] A composite organic improver of the present invention is composed of a compound A and a compound B, wherein the compound A is a compound of formula (I-1), N,N'-diphenyloxalyl diamide, which is a monooxalyl diamide derivative, and the compound B is a compound of formula (II-1), N-phenyl-N'-(6-((oxy(phenylamino)acetyl)amino)hexyl)oxalyl diamide, which is a bisoxalyl diamide derivative. The compounds A and B can induce ethylene polymer molecular chains to form variant spherulites through self-assembly heterogeneous nucleation, and the variant spherulites include a central bright region and an extinction dark region, wherein the extinction dark region surrounds the central bright region.
[0111] The structural formula of compound A is as follows:
[0112]
[0113] The structural formula of compound B is as follows:
[0114]
[0115] In this embodiment, the mass ratio of compound A to compound B is 250:750.
[0116] In this embodiment, the composite organic improver has the following characteristics:
[0117] (1) The peak position W of the characteristic absorption peak of the NH bending and CN stretching coupled vibration present in the infrared spectrum of compound A of formula (I-1) within the range of 1600 to 1400 wavenumbers is located at 1515 wavenumbers, and the peak position W of the characteristic absorption peak of the NH bending and CN stretching coupled vibration present in the infrared spectrum of compound B of formula (II-1) within the range of 1600 to 1400 wavenumbers is located at 1529 wavenumbers, and the difference ΔW between the two is 14 wavenumbers, not exceeding 15 wavenumbers;
[0118] (2) The composite organic improver has a characteristic absorption peak of NH stretching vibration in the range of 3500-3100 wavenumbers of the infrared spectrum, and a characteristic absorption peak of carbonyl stretching vibration in the range of 1700-1600 wavenumbers;
[0119] (3) The melting point range of the composite organic improver is 230-280℃;
[0120] (4) The composite organic improver is heated from 25°C to a molten state and then cooled to 25°C to form a fibrous structure;
[0121] (5) The composite organic modifier is characterized by two-stage thermal weight loss under thermogravimetric analysis: the first-stage thermal weight loss temperature range is 100-300℃ and the second-stage thermal weight loss temperature range is 280-333℃.
[0122] In this embodiment, the characteristics of the variant spherulites are shown in Example 4 of Table 2.
[0123] Preparation method 1
[0124] A method for preparing the composite organic improver of this embodiment adopts preparation method 1, comprising the following steps:
[0125] S1. In a reactor equipped with a stirrer, a thermometer, a heating device, a dropping device and a condenser, 375.5 g (2.57 mol) of diethyl oxalate was added, and at room temperature (about 25° C.), a solution consisting of 116.2 g (1 mol) of hexamethylenediamine and 116 mL of ethanol was added dropwise to the diethyl oxalate to react to obtain a first reaction mixture;
[0126] S2. 900 mL of N,N-dimethylformamide (DMF) was added to the first reaction mixture and heated until the mixture was dissolved. Then, a solution consisting of 338.9 g (3.64 mol) of aniline and 113 mL of DMF was added and refluxed at 60° C. to 85° C. The excess value n of the monoamine was 0.5 mol. After completion of the reaction, the obtained second reaction mixture was filtered, washed, and dried for purification and separation to obtain a composite organic improver in the form of a white powder and a block product (which can be subsequently crushed), designated EX1-1, with a yield of 92.1%.
[0127] According to thermogravimetric analysis, the weight loss rates of the compound of formula (I-1) and the compound of formula (II-1) in EX1-1 were approximately 25% and 75%, respectively, and the mass ratio between the two was approximately 250:750.
[0128] Dimethyl sulfoxide (DMSO) is a good solvent for compounds of formula (I-1) and (II-1), but the byproducts are insoluble in DMSO. A 10g sample of product EX1-1 was mixed with 500ml of DMSO, revealing that most of the product dissolved. After filtration, washing, and drying, approximately 0.4g of insoluble matter was found, indicating that the byproducts comprised approximately 4% of EX1-1.
[0129] Preparation method 2
[0130] A method for preparing the composite organic improver of this embodiment adopts preparation method 2, comprising the following steps:
[0131] S1. In a reactor equipped with a stirrer, a thermometer, a heating device, a dropping device and a condenser, 146.1 g (1 mol) of diethyl oxalate was added. At room temperature (about 25° C.), a solution consisting of 113.6 g (1.22 mol) of aniline and 300 mL of ethanol was added dropwise to the diethyl oxalate to react. After completion of the reaction, a reaction intermediate was obtained.
[0132] S2. 700 mL of DMF was added to the reaction intermediate, heated to dissolve, and then a solution consisting of 45.3 g (0.39 mol) of hexamethylenediamine and 100 mL of DMF was slowly added and refluxed at 60° C. to 85° C. After completion of the reaction, the mixture was filtered, washed, and dried to obtain a composite organic improver in the form of a white powder and a block product, designated as EX1-2, with a yield of 93.6%.
[0133] Thermogravimetric analysis revealed that the weight loss rates of the compound of formula (I-1) and the compound of formula (II-1) in EX1-2 were approximately 25% and 75%, respectively, with a mass ratio of approximately 250:750. Dissolving 10 g of the product EX1-2 in 500 ml of DMSO revealed that EX1-2 was almost completely dissolved. After filtration, washing, and drying, the filter cake contained very little insoluble matter, making it difficult to weigh. Byproducts in EX1-2 accounted for no more than 0.1%.
[0134] Example 2
[0135] A composite organic improver of the present invention is composed of compound A and compound B, wherein compound A is N,N'-diphenyloxalyldiamide, a compound of formula (I-1), and compound B is N-phenyl-N'-(6-((oxy(phenylamino)acetyl)amino)hexyl)oxalyldiamide, a compound of formula (II-1). Compound A and compound B can induce ethylene polymer molecular chains to form variant spherulites through self-assembly heterogeneous nucleation, and the variant spherulites include a central bright area and an extinction dark area, and the extinction dark area surrounds the central bright area.
[0136] In this embodiment, the mass ratio of compound A to compound B is 500:500.
[0137] In this embodiment, the composite organic improver has the following characteristics:
[0138] (1) The difference ΔW between the peak positions of the characteristic absorption peaks of the NH bending and CN stretching coupling vibrations present in the infrared spectrum of compound A of formula (I-1) and compound B of formula (II-1) in the range of 1600 to 1400 wavenumbers is 14 wavenumbers and does not exceed 15 wavenumbers;
[0139] (2) The composite organic improver has a characteristic absorption peak of NH stretching vibration in the range of 3500-3100 wavenumbers of the infrared spectrum, and a characteristic absorption peak of carbonyl stretching vibration in the range of 1700-1600 wavenumbers;
[0140] (3) The melting point range of the composite organic improver is 230-284℃;
[0141] (4) The composite organic improver is heated from 25°C to a molten state and then cooled to 25°C to form a fibrous structure;
[0142] (5) The composite organic modifier is characterized by two-stage thermal weight loss under thermogravimetric analysis: the first-stage thermal weight loss temperature range is 100-300℃ and the second-stage thermal weight loss temperature range is 280-333℃.
[0143] In this embodiment, the characteristics of the modified spherulites are shown in Example 5 of Table 2.
[0144] Preparation method 1
[0145] A method for preparing a composite organic improver of the present invention adopts preparation method 1 and comprises the following steps:
[0146] S1. In a reactor equipped with a stirrer, a thermometer, a heating device, a dropping device and a condenser, 542.0 g (3.71 mol) of diethyl oxalate was added, and at room temperature (about 25° C.), a solution consisting of 116.2 g (1 mol) of hexamethylenediamine and 116 mL of ethanol was added dropwise to the diethyl oxalate to react to obtain a first reaction mixture;
[0147] S2. 900 mL of DMF was added to the first reaction mixture and heated until the mixture was dissolved. A solution consisting of 551.0 g (5.92 mol) of aniline and 276 mL of DMF was then added and refluxed at 60° C. to 85° C. The excess monoamine value n was 0.5 mole. After completion of the reaction, the resulting second reaction mixture was purified and separated by filtration, washing, and drying to obtain a composite organic improver in the form of a white powder and a block product, designated EX2-1, with a yield of 96.5%.
[0148] Thermogravimetric analysis revealed that the weight loss rates of compound (I-1) and compound (II-1) in EX2-1 were approximately 50% and 50%, respectively, with a mass ratio of approximately 500:500. A 10g solution of EX2-1 in 500ml of DMSO showed that the vast majority of EX2-1 dissolved. After filtration, washing, and drying, approximately 0.08g of insoluble matter was found, indicating that the byproducts in EX2-1 accounted for approximately 0.8%.
[0149] Preparation method 2
[0150] A method for preparing the composite organic improver of this embodiment adopts preparation method 2, comprising the following steps:
[0151] S1. In a reactor equipped with a stirrer, a thermometer, a heating device, a dropping device and a condenser, 146.1 g (1 mol) of diethyl oxalate was added. At room temperature (about 25° C.), a solution consisting of 136.0 g (1.46 mol) of aniline and 300 mL of ethanol was added dropwise to the diethyl oxalate to react. After completion of the reaction, a reaction intermediate was obtained.
[0152] S2. 700 mL of DMF was added to the reaction intermediate, and the mixture was heated until dissolved. A solution consisting of 31.4 g (0.27 mol) of hexamethylenediamine and 100 mL of DMF was slowly added and refluxed at 60° C. to 85° C. After completion of the reaction, the mixture was purified and separated by filtration, washing, and drying to obtain a composite organic improver in the form of white powder and blocks, designated as EX2-2, with a yield of 92.9%.
[0153] Thermogravimetric analysis revealed that the weight loss rates of the compound of formula (I-1) and the compound of formula (II-1) in EX2-2 were approximately 50% and 50%, respectively, with a mass ratio of approximately 500:500. Dissolving 10 grams of EX2-2 in 500 milliliters of DMSO revealed that EX2-2 dissolved almost completely, with no insoluble matter remaining. Byproducts in EX2-2 accounted for less than 0.1%.
[0154] Example 3
[0155] A composite organic improver of the present invention is composed of compound A and compound B, wherein compound A is N,N'-diphenyloxalyldiamide, a compound of formula (I-1), and compound B is N-phenyl-N'-(6-((oxy(phenylamino)acetyl)amino)hexyl)oxalyldiamide, a compound of formula (II-1). Compound A and compound B can induce ethylene polymer molecular chains to form variant spherulites through self-assembly heterogeneous nucleation, and the variant spherulites include a central bright area and an extinction dark area, and the extinction dark area surrounds the central bright area.
[0156] In this embodiment, the mass ratio of compound A to compound B is 750:250.
[0157] In this embodiment, the composite organic improver has the following characteristics:
[0158] (1) The difference ΔW between the peak positions of the characteristic absorption peaks of the NH bending and CN stretching coupling vibrations present in the infrared spectrum of compound A of formula (I-1) and compound B of formula (II-1) in the range of 1600 to 1400 wavenumbers is 14 wavenumbers and does not exceed 15 wavenumbers;
[0159] (2) The composite organic improver has a characteristic absorption peak of NH stretching vibration in the range of 3500-3100 wavenumbers of the infrared spectrum, and a characteristic absorption peak of carbonyl stretching vibration in the range of 1700-1600 wavenumbers;
[0160] (3) The melting point range of the composite organic improver is 230-288℃;
[0161] (4) The composite organic improver is heated from 25°C to a molten state and then cooled to 25°C to form a fibrous structure;
[0162] (5) The composite organic modifier is characterized by two-stage thermal weight loss under thermogravimetric analysis: the first-stage thermal weight loss temperature range is 100-300℃ and the second-stage thermal weight loss temperature range is 280-333℃.
[0163] In this embodiment, the characteristics of the variant spherulites are shown in Example 6 of Table 2.
[0164] Preparation method 1
[0165] A method for preparing the composite organic improver of this embodiment adopts preparation method 1, comprising the following steps:
[0166] S1. In a reactor equipped with a stirrer, a thermometer, a heating device, a dropping device and a condenser, 1041.3 g (7.13 mol) of diethyl oxalate was added, and at room temperature (about 25° C.), a solution consisting of 116.2 g (1 mol) of hexamethylenediamine and 116 mL of ethanol was added dropwise to the diethyl oxalate to react to obtain a first reaction mixture;
[0167] S2. 900 mL of DMF was added to the first reaction mixture and heated until dissolved. Then, a solution consisting of 1187.5 g (12.76 mol) of aniline and 396 mL of DMF was added and refluxed at 60° C. to 85° C. The excess of monoamine, n, was 0.5 mol. After completion of the reaction, the resulting second reaction mixture was purified and separated by filtration, washing, and drying to obtain a composite organic improver in the form of white powder and blocks, designated as EX3-1, with a yield of 93.0%.
[0168] Thermogravimetric analysis revealed that the weight loss rates of the compound of formula (I-1) and the compound of formula (II-1) in EX3-1 were approximately 75% and 25%, respectively, with a mass ratio of approximately 750:250. Dissolving 10 g of EX3-1 in 500 ml of DMSO revealed that EX3-1 was almost completely dissolved. After filtration, washing, and drying, the filter cake contained very little insoluble matter, making it difficult to weigh. Byproducts in EX3-1 accounted for no more than 0.1%.
[0169] Preparation method 2
[0170] A method for preparing the composite organic improver of this embodiment adopts preparation method 2, comprising the following steps:
[0171] S1. In a reactor equipped with a stirrer, a thermometer, a heating device, a dropping device and a condenser, 146.1 g (1 mol) of diethyl oxalate was added. At room temperature (about 25° C.), a solution consisting of 160.2 g (1.72 mol) of aniline and 300 mL of ethanol was added dropwise to the diethyl oxalate to react. After completion of the reaction, a reaction intermediate was obtained.
[0172] S2. 700 mL of DMF was added to the reaction intermediate, heated until dissolved, and a solution consisting of 16.3 g (0.14 mol) of hexamethylenediamine and 100 mL of DMF was slowly added and refluxed at 60° C. to 85° C. After completion of the reaction, the mixture was purified and separated by filtration, washing, and drying to obtain a composite organic improver in the form of white powder and blocks, designated as EX3-2, with a yield of 93.5%.
[0173] Thermogravimetric analysis revealed that the weight loss rates of the compound of formula (I-1) and the compound of formula (II-1) in EX3-2 were approximately 75% and 25%, respectively, with a mass ratio of approximately 750:250. Dissolving 10 g of EX3-2 in 500 ml of DMSO revealed that EX3-2 dissolved almost completely, with no insoluble matter remaining. Byproducts accounted for less than 0.1% of the total EX3-2 content.
[0174] Comparative Example 1
[0175] A monooxalyl diamide derivative, specifically the compound N,N'-diphenyloxalyl diamide of formula (I-1), is recorded as comparative example CT1.
[0176] Comparative Example 2
[0177] A bisoxalyl diamide derivative, specifically the compound of formula (II-1) N-phenyl-N'-(6-((oxy(phenylamino)acetyl)amino)hexyl)oxalyl diamide, is recorded as comparative example CT2.
[0178] Comparative Example 3
[0179] Commercially available Millad 3988 was recorded as comparative example CT3.
[0180] Comparative Example 4
[0181] A method for preparing a composite organic improver is substantially the same as the preparation method 1 of Example 1, except that in step S1, 306.8 g (2.1 mol) of diethyl oxalate is used, the reaction temperature is 70°C, and in step S2, 251.3 g (2.7 mol) of aniline is used. The resulting composite organic improver is in the form of a white powder and a block, designated as Comparative Example CT4, with a yield of 90.3%. The composite organic improver comprises compound A, compound B, and a byproduct. Compound A is N,N'-diphenyloxalyldiamide (Formula (I-1), compound B is N-phenyl-N'-(6-((oxy(phenylamino)acetyl)amino)hexyl)oxalyldiamide (Formula (II-1), and the byproduct is a polymer.
[0182] According to thermogravimetric analysis, the weight loss rates of the compound of formula (I-1), the compound of formula (II-1) and the polymer by-product in CT4 were approximately 16.6%, 56.7% and 26.7%, respectively, and the mass ratio of the three was approximately 166:567:267.
[0183] 10 g of the product CT4 was mixed with 500 ml of DMSO. The results showed that CT4 could not be completely dissolved. After filtering, washing, and drying, it was found that the insoluble matter was 2.7 g, that is, the proportion of by-products in the comparative example CT4 was about 27%.
[0184] Based on the beneficial effects of the one-pot method, the yield of the composite organic improver obtained by the preparation method in the above Examples 1-3 is generally above 90%. The reaction involved in step S1 in preparation method 1 may generate a polymer by-product (such as Formula VII), and the reaction in step S2 may generate a polymer by-product (such as Formula VIII). The proportion of by-products in comparative example CT4 is about 27%, and the proportion of by-products in EX1-1, EX2-1, and EX3-1 prepared by preparation method 1 of the present invention is 4%, 0.8%, and no more than 0.1%, respectively. Multiple experiments have shown that: (1) when the molar ratio m of the raw material oxalic acid diester to the diamine in step S1 is in the range of 2<m<2.5 and the reaction temperature is between 70℃ and close to the reflux temperature, more by-products (such as Formula VII) will be generated, and more polymer by-products (such as Formula VIII) will be generated after the reaction in step S2; (2) when the raw material molar ratio m in step S1 is in the range of m≥2.5 and the reaction temperature is not higher than 40℃, the by-products (such as Formula VII) are greatly reduced, and the polymer by-products (such as Formula VIII) generated after the reaction in step S2 are less; (3) when the raw material molar ratio m in step S1 is in the range of m>1000, the proportion of compound A in the composite organic improver generated after the reaction in step S2 is close to 100%, and this value range is negligible. Therefore, the preparation method 1 of the present invention can reduce or avoid the generation of polymer by-products by controlling the process parameters.
[0185]
[0186] The reaction involved in Preparation Method 2 occurs between a bifunctional raw material and a monofunctional raw material, and there are few by-products. For example, the proportion of by-products in EX1-2, EX2-2, and EX3-2 is relatively low. Therefore, Preparation Method 2 of the present invention reduces or avoids the production of polymeric by-products by optimizing the process. In addition, Preparation Method 2 lacks one type of starting raw material acid-binding agent (such as triethylamine) compared to the prior art.
[0187] The composite organic improver obtained in Examples 1-3 was tested for its infrared spectrum by Fourier transform infrared spectrometer, the heat-treated composite organic improver was observed by polarizing microscope, its melting point and crystallization peak temperature were tested by differential scanning calorimetry (DSC), and its thermal weight loss temperature was tested by thermogravimetric analyzer (nitrogen atmosphere, heating rate of 10°C / min). The test results are as described in Examples 1-3, and the results show that the composite organic improver composed of different weight parts of the compound of formula (I-1) and the compound of formula (II-1) all have a higher melting point and a higher thermal weight loss temperature.
[0188] Depend on Figure 1 It can be seen that the composite organic improver composed of compound A and compound B has a narrow and strong absorption peak in the wavenumber range of 3500-3100 in the infrared spectrum, which belongs to the characteristic absorption peak of NH stretching vibration, also known as the amide A band; there is a narrow and strongest absorption peak in the wavenumber range of 1700-1600, which belongs to the characteristic absorption peak of carbonyl stretching vibration, also known as the amide I band; there is a narrow and strong absorption peak in the wavenumber range of 1600-1400, which belongs to the characteristic absorption peak of coupled vibration of NH bending and CN stretching, also known as the amide II band.
[0189] Depend on Figure 2 It can be seen that the intensity of the characteristic absorption peak of the NH stretching vibration of the composite organic modifier increases with the increase in the mass fraction of compound B. This indicates that the strength of the intermolecular hydrogen bonding can be adjusted by adjusting the ratio of compound A to compound B.
[0190] As shown in Table 1, CT1 is a monooxalyl diamide compound with a simple structure and low cost, while CT2 is a bisoxalyl diamide compound with a unique and complex structure and high cost. Due to the beneficial effects of the one-pot synthesis process, the composite organic improvers prepared by Preparation Methods 1 and 2 are less expensive than CT2 in Comparative Example 2, and the cost is further reduced compared to a simple physical mixture of CT1 and CT2.
[0191] Table 1 Cost comparison of the composite organic improvers obtained by different preparation methods in Examples 1-3 and Comparative Examples 1-2
[0192]
[0193] The above-mentioned composite organic improver can further illustrate that the composite organic improver of the present invention has the beneficial effects of short process steps, low cost, good compatibility, good thermal stability at high processing temperature, and adjustable intermolecular hydrogen bonds as an additive for ethylene polymers.
[0194] Example 4
[0195] An application of the composite organic improver of the present invention as a polymer additive, specifically as an ethylene polymer additive, comprises the following preparation steps:
[0196] (1) The composite organic improver EX1-1 was mixed with a density of 0.920 g / cm 3 an ethylene copolymer (comonomer 1-butene, trade name linear low density polyethylene polymer, melting point 124° C., melt flow index >1 g / 10 min, medium melt index resin) in a ratio of 0.1:100 by mass, and premixed uniformly to obtain a mixed material;
[0197] (2) The mixture was melt-blended in a screw extruder at 200°C (76°C above the melting point) for 3 minutes, and then cooled to room temperature (25°C) at a cooling rate of 50°C / min, so that compound A and compound B in the composite organic improver induced the molecular chains of the ethylene polymer to form variant spherulites through self-assembly heterogeneous nucleation, thereby obtaining an ethylene polymer composition, which was recorded as M1. The variant spherulites formed by crystallization of the composition M1 after melting, such as Figure 3 and as shown in Table 2.
[0198] Example 5
[0199] A composite organic improver of the present invention is used as a polymer additive, specifically as an additive for ethylene polymers. The preparation steps are essentially the same as those in Example 4, except that EX2-1 is used as the composite organic improver to produce an ethylene polymer composition, designated M2. Crystallization of this composition M2 after melting yields modified spherulites, the characteristics of which are shown in Table 2.
[0200] Example 6
[0201] The composite organic improver of the present invention is used as a polymer additive, specifically as an ethylene polymer additive. The preparation steps are basically the same as those in Example 4, except that the composite organic improver used is EX3-1, and an ethylene polymer composition is obtained, which is denoted as M3. The composition M3 is melted and crystallized to form modified spherulites, such as Figure 4 and as shown in Table 2.
[0202] Comparative Example 5
[0203] In this comparative example, no additives were used and the ethylene polymer used was the same as in Example 4. The pure ethylene copolymer was designated as O1. The spherulites formed by the crystallization of the pure ethylene copolymer O1 after melting were typical black cross matt spherulites with a size of less than 10 microns. Figure 5 shown.
[0204] Comparative Example 6
[0205] A method for using CT1 as a polymer additive, specifically as an ethylene polymer additive, is described in Example 4, wherein the preparation steps are substantially the same as those in Example 4, except that CT1 is used as the additive to obtain an ethylene polymer composition, designated as O2. The composition O2 is melted and crystallized to form spherulites similar in shape and size to the pure ethylene copolymer O1. Figure 6 shown.
[0206] Comparative Example 7
[0207] An application of CT2 as a polymer additive, specifically as an ethylene polymer additive, is prepared in the same manner as in Example 4, except that the additive used is CT2, and an ethylene polymer composition is obtained, designated as O3. Figure 7 As shown, the spherulites formed by the crystallization of the composition O3 after melting are mainly homogeneous nucleation. It can be observed that although the additive CT2 forms a fibrous structure, its morphology and size are different from those of the mutant spherulites, and no mutant spherulites are generated.
[0208] Comparative Example 8
[0209] A method for using CT3 as a polymer additive, specifically as an ethylene polymer additive, is described. The preparation steps are essentially the same as those in Example 4, except that CT3 is used as the additive to produce an ethylene polymer composition, designated O4. Upon melting and crystallization of composition O4, no aberrant spherulites are formed.
[0210] Comparative Example 9
[0211] A method for using CT3 as a polymer additive, specifically as an ethylene polymer additive, is described. The preparation steps are substantially the same as those in Example 4, with the following differences: (1) CT3 is used as the additive, and (2) the mass ratio of CT3 to ethylene copolymer is 0.2:100, resulting in an ethylene polymer composition, designated O5. Upon crystallization of composition O5 after melting, no aberrant spherulites are formed.
[0212] Regarding the characterization method of ethylene polymer compositions:
[0213] An injection molding machine was used to injection mold the ethylene polymer composition into a standard transmittance turbidity sheet with a thickness of 1 mm in accordance with GB / T 17037.3-2003, a standard tensile specimen with a thickness of 4 mm in accordance with GB / T 1040.2-2006, and a standard bending specimen and a standard notched impact specimen with a thickness of 4 mm in accordance with GB / T17037.1-2019.
[0214] The crystallization and melting parameters of each ethylene polymer composition were measured using a differential scanning calorimeter (DSC) in accordance with GB / T 19466.3-2004. The DSC non-isothermal temperature program for obtaining the peak crystallization temperature (Tc) was as follows: a sample was collected from a target portion, and under nitrogen protection, the temperature was raised from 25°C to 200°C at a rate of 10°C / min, held at 200°C for 3 minutes, and then cooled to 25°C at a rate of 10°C / min. The DSC isothermal temperature program for obtaining the half-crystallization time was as follows: a sample was collected from a target portion, and under nitrogen protection, the temperature was raised from 25°C to 160°C at a rate of 50°C / min, held at 160°C for 5 minutes, and then cooled to 108.5°C at a rate of 50°C / min, followed by isothermal crystallization for 30 minutes.
[0215] Optical properties testing was conducted according to GB / T 2410-2008 for light transmittance and turbidity. Tensile properties testing was conducted according to GB / T 1040.2-2006 for tensile properties. Flexural properties testing was conducted according to GB / T 9341-2008. Impact properties testing was conducted according to GB / T 1843-2008 for notched Izod impact strength.
[0216] Characterization results of ethylene polymer compositions:
[0217] When preparing ethylene polymer compositions M1 to M3, it was found that the composite organic improvers EX1 to EX3 dissolved in the ethylene copolymer melt at high temperature, resulting in a transparent melt with good compatibility and uniform dispersion. During the subsequent cooling period, the crystallization of the ethylene copolymer composition was a coexistence mode of mainly heterogeneous nucleation and supplemented by homogeneous nucleation, such as Figure 3-4 Different from the effect of increasing nucleation density and reducing spherulite size in traditional heterogeneous nucleation, the composite organic improver of the present invention has the effect of reducing nucleation density and increasing variant spherulite size in heterogeneous nucleation of ethylene polymer, as shown in Table 2 and Figure 3-7 The composite organic improver induces the ethylene copolymer molecular chain to form variant spherulites through self-assembly heterogeneous nucleation, and the areas between the variant spherulites are small spherulites formed by homogeneous nucleation of the ethylene copolymer.
[0218] Table 2 Characteristics of the variant spherulites in Examples 4 to 6 and Example 8 and the spherulites in Comparative Examples 5 to 9 and Comparative Example 11
[0219]
[0220] Table 2 lists the morphological characteristics of the modified spherulites of the example composition and the spherulites of the comparative example composition. Figure 3-4 and Figure 5-7Their morphologies under a polarizing microscope are shown respectively. The ethylene polymer compositions M1 and M3 using EX1-1 and EX3-1 both have a crystalline morphology of variant spherulites, and the ethylene polymer composition M2 using EX2-1 has a variant spherulite morphology similar to M1 and M3. This variant spherulite mainly includes two parts: a central bright area and an extinction dark area, and the extinction dark area surrounds the central bright area. The characteristics of this variant spherulite are as follows: (1) The overall morphology of the variant spherulites in the embodiments is spherical or quasi-spherical, while in the prior art, including the comparative example, as the small spherulites of ethylene polymer grow, adjacent small spherulites collide to form irregular polygonal spherulites; (2) The maximum diameter of the variant spherulites in the embodiments is in the range of 20 microns to 500 microns, which is larger than the diameter of the pure ethylene copolymer spherulites in comparative example 1, and the diameter of the spherulites tends to increase, while the additives (such as CT1-CT3) increase the number of crystal nuclei O2-O5 in the comparative example composition, and the diameter of the spherulites tends to decrease; (3) The central bright area of the variant spherulites in the embodiments is composed of one or more needle-like units, narrow The embodiment of the invention is composed of dumbbell-shaped units or bundle-shaped units, while the prior art, including the bright area of the spherulites in the comparative examples, is not in the central position, and the relative area of the bright area is larger and mostly petal-shaped; (4) The central bright area of the variant spherulites in the embodiment extends radially outward from the center; (5) The shape of the extinction dark area of the variant spherulites in the embodiment includes one or more of a double semicircle, an oval, a circle, a jujube-shaped circle and an oblate circle, which is significantly different from the prior art, including the black cross extinction pattern in the comparative examples; (6) Another notable feature of the variant spherulites in the embodiment is the proportion of the extinction dark area to the total area of the variant spherulites, which is 50% to 95%, which is greater than the proportion of the extinction dark area of the spherulites in the comparative examples.
[0221] In the present invention, the composition, morphology and size of the variant spherulites are different from the conventional black cross matte spherulites in the comparative example, and are also different from the spherulites in the prior art. Figure 3 As shown, the spherical variant spherulites with a maximum diameter of 20-100 μm mainly include two parts: a central bright area and an extinction dark area. The extinction dark area surrounds the central bright area. The central bright area is mainly distributed in the 3π / 4 and / or 7π / 4 angle areas, and the bright area is significantly weakened radially. There is almost no bright area in other angle areas, and the extinction dark area accounts for about 93.0%. Figure 4 The central bright area of the medium-variant spherulite is mainly distributed at angles of π / 4 and / or 5π / 4, and the bright area is significantly weakened radially, and there is almost no bright area in other angle areas.
[0222] Based on the beneficial effects of the formed variant spherulites, the crystallization peak temperature, half-crystal time, light transmittance, turbidity, tensile properties, bending properties, and impact properties of each ethylene polymer composition sample are shown in Table 3.
[0223] Table 3 Performance results of ethylene polymer compositions of Examples 4 to 6, Example 8, Comparative Examples 5 to 9, and Comparative Example 11
[0224]
[0225]
[0226] The ethylene polymer compositions prepared in the above examples did not exhibit undesirable yellowing and precipitation after processing.
[0227] As shown in Table 3, compared to pure ethylene copolymers without additives, the ethylene copolymers containing EX1-1 to EX3-1 exhibited crystallization temperatures exceeding 5°C higher, half-crystallization times within 30 seconds, and turbidity values below 44%, with turbidity reductions of 44-49%. The tensile strain at break and notched impact strength, representing toughness, increased by 7-11% and 7-9%, respectively, while flexural strength, representing rigidity, also saw a slight increase. Rigidity and toughness are generally in conflict with each other in polymers; increased toughness typically results in decreased rigidity. The improved rigidity and toughness of the compositions of the present invention demonstrate that ethylene polymer compositions containing composite organic modifiers possess superior mechanical properties. Furthermore, the tensile strength increased by approximately 5%, also demonstrating superior mechanical properties. Compared to a commercially available product (Millad 3988), the ethylene polymer compositions containing EX1-1 to EX3-1 exhibit significant improvements in crystallization temperature, half-crystallization time, transmittance, turbidity, tensile strength, tensile strain at break, flexural strength, and notched impact strength. More importantly, the composite organic improver of the present invention achieves enhanced performance in ethylene polymer compositions while requiring a lower dosage than a commercially available product (Millad 3988). Compared to pure monooxalyldiamide compound CT1 and pure bisoxalyldiamide compound CT2, the composite organic improver employed in the present invention demonstrates significant improvements in the crystallization temperature, half-crystallization time, light transmittance, turbidity, tensile strength, tensile strain at break, and notched impact strength of ethylene copolymers.
[0228] Example 7
[0229] A composite organic improver of the present invention is composed of compound A and compound B, wherein compound A is N,N'-diphenyloxalyldiamide of formula (I-1), and compound B is N-phenyl-N'-(8-((oxy(phenylamino)acetyl)amino)octyl)oxalyldiamide of formula (II-2), and compounds A and B can induce ethylene polymer molecular chains to form variant spherulites through self-assembly heterogeneous nucleation, wherein the variant spherulites include a central bright region and an extinction dark region, wherein the extinction dark region surrounds the central bright region;
[0230] The structural formula of compound B is as follows:
[0231]
[0232] In this embodiment, the mass ratio of compound A to compound B is 250:750.
[0233] In this embodiment, the composite organic improver has the following characteristics:
[0234] (1) The peak position W of the characteristic absorption peak of the NH bending and CN stretching coupling vibration of compound B of formula (II-2) in the infrared spectrum within the range of 1600 to 1400 wavenumbers is located at 1516 wavenumbers, and the difference ΔW between the peak position W and the compound of formula (I-1) is 1 wavenumber and does not exceed 5 wavenumbers;
[0235] (2) The composite organic improver has a characteristic absorption peak of NH stretching vibration in the range of 3500-3100 wavenumbers of the infrared spectrum, and a characteristic absorption peak of carbonyl stretching vibration in the range of 1700-1600 wavenumbers;
[0236] (3) The melting point range of the composite organic improver is 200℃~244℃;
[0237] (4) The composite organic improver is heated from 25°C to a molten state and then cooled to 25°C to form a fibrous structure;
[0238] (5) The composite organic modifier is characterized by two-stage thermal weight loss under thermogravimetric analysis: the first-stage thermal weight loss temperature range is 100℃~300℃ and the second-stage thermal weight loss temperature range is 320℃~370℃.
[0239] In this embodiment, the characteristics of the variant spherulites are shown in Example 8 in Table 2.
[0240] Preparation method 1
[0241] A preparation method of a composite organic improver of the present invention is prepared by referring to Preparation Method 1 in Example 1, wherein the oxalic acid diester is 381.2 g (2.61 mol) of diethyl oxalate, the diamine is 144.3 g (1 mol) of octanediamine, the monoamine is 346.1 g (3.72 mol) of aniline, the monoamine excess value n is 0.5 mol, and other process conditions remain unchanged. After completion of the reaction, the product is purified and separated by filtration, washing, drying, etc. to obtain a white powder and a block product, which is recorded as EX4, with a yield of 90.6%.
[0242] Thermogravimetric analysis revealed that the weight loss rates of compound (I-1) and compound (II-2) in EX4 were approximately 25% and 75%, respectively, with a mass ratio of approximately 250:750. DMSO is also a good solvent for compound (II-2), and the byproduct is insoluble in DMSO. A 10g solution of product EX4 mixed with 500ml of DMSO showed that most of the EX4 dissolved. After filtration, washing, and drying, the insoluble matter was found to be approximately 0.3g, indicating that the byproduct constituted approximately 3% of the EX4.
[0243] Comparative Example 10
[0244] A bisoxalyl diamide derivative, specifically the compound N-phenyl-N'-(8-((oxy(phenylamino)acetyl)amino)octyl)oxalyl diamide, as shown in formula (II-2), is recorded as comparative example CT5.
[0245] The oxalyl group exhibits a specific coplanar structure that facilitates the formation of a quasi-conjugated proton system. The NH bending and CN stretching coupled vibrations (amide II band) are located closer to the substituent groups (R1, R2, R3, R4, and R5) along the molecular axis, making them more susceptible to their influence. In other words, the amide II band is particularly sensitive to polymorphism caused by differences in molecular chain conformation. Therefore, the NH bending and CN stretching coupled vibration absorption peaks were selected as indicators for determining the quality of the additives used in this invention.
[0246] Different substituent groups (R1, R2, R3, R4, R5) result in varying degrees of twisting of the molecular chains of Compound A and / or Compound B, which can cause the fully extended zigzag conformation to tilt or twist. Increased chain conformational twisting affects the planarity of the quasi-conjugated system to a certain extent, thereby separating different types of superstructures or developing different subcrystalline states. This tilt or twisting of the coplanar structure, influenced by the substituent groups, affects the matching between the two components of the composite organic modifier and further influences self-assembly and the resulting fibrous structure. A significant macroscopic manifestation of this effect is the shift in the position of the amide II band. This polymorphic difference caused by the substituent groups also affects the formation of variant spherulites of ethylene polymers growing with the composite organic modifier as the crystal nucleus, further affecting their crystallization behavior and macroscopic properties. Compounds A and B with higher matching rates are more suitable for the growth of ethylene polymer molecular chains into variant spherulites. Therefore, in order to obtain an ethylene polymer composition with a higher crystallization temperature, a shorter half-crystallization time, a lower turbidity, and more significant mechanical properties, the difference ΔW between the peak positions of the characteristic absorption peaks of the NH bending and CN stretching coupling vibrations present in the infrared spectrum range of 1600 to 1400 wavenumbers between Compound A and Compound B of the present invention is preferably no more than 15 wavenumbers, more preferably no more than 10 wavenumbers, and further preferably no more than 5 wavenumbers, so as to achieve a higher matching rate between Compound A and Compound B. The monooxalyl diamine components in EX1-1 and EX4 are both compounds of formula (I-1), the bisoxalyl diamine components are compounds of formula (II-1) and formula (II-2), respectively, and CT1, CT2, and CT5 have the structures of formula (I-1), formula (II-1), and formula (II-2), respectively. Figure 8 The infrared spectra of EX1-1, EX4, CT1, CT2, and CT5 in the 1600-1400 wavenumber range (displayed as 1580-1470 wavenumber range) are shown. Figure 8 It can be seen that the characteristic absorption peaks of NH bending and CN stretching coupled vibration in the wavenumber range of 1600-1400 for CT1 and CT2 are located at 1515 and 1529 wavenumbers, respectively, and the difference △W between the two peak positions is 14 wavenumbers, which are far apart. In addition, EX1-1 composed of two components has a shoulder peak at 1515 wavenumber. Compared with EX1-1, the characteristic absorption peak of NH bending and CN stretching coupled vibration of compound B component CT5 in EX4 is located at 1516 wavenumber, and the difference △W between this peak position and the peak position of CT1 is 1 wavenumber, which is even smaller and almost overlaps. The absorption peak position of EX4 composed of two components is also at 1515 wavenumber, showing a higher matching rate between the components.
[0247] Another beneficial effect of the higher matching rate is that the composite organic improver forms a developed fibrous structure after heat treatment, with the diameter of the single fiber ranging from 0.1 to 10 microns, such as Figure 9 Conversely, the well-developed fibrous structure also indicates a high matching rate between compound A and compound B.
[0248] Example 8
[0249] The composite organic improver of the present invention is used as a polymer additive, specifically as an ethylene polymer additive. The preparation steps are basically the same as those in Example 4, except that the composite organic improver used is EX4, and an ethylene polymer composition is obtained, which is denoted as M4. The composition M4 is melted and crystallized to form a modified spherulite, such as Figure 10 shown.
[0250] Comparative Example 11
[0251] CT5 was used as a polymer additive, specifically as an ethylene polymer additive. The preparation steps were essentially the same as those in Example 4, except that CT5 was used as the additive to produce an ethylene polymer composition, designated O6. Spherulites formed by melting and crystallizing this composition O6 were primarily homogeneous nucleation. Although CT6 could also form a fibrous structure like CT2, it did not form aberrant spherulites.
[0252] Characterization results of ethylene polymer compositions:
[0253] When preparing composition M4, it was found that EX4 dissolved in the ethylene copolymer melt at high temperature, resulting in a transparent melt with good compatibility and uniform dispersion. During the subsequent cooling period, the crystallization of composition M4 was characterized by a coexistence of heterogeneous nucleation as the primary and homogeneous nucleation as the secondary. The composite organic modifier induced the ethylene copolymer molecular chains to form variant spherulites through self-assembled heterogeneous nucleation. The resulting variant spherulites had the effect of low nucleation density and large variant spherulite size. One variant spherulite had a diameter of 184 microns, which was also confirmed by subsequent scanning electron microscopy results, as shown in Figure 2. Figure 10 Under the same conditions, the spherulites formed by homogeneous nucleation of ethylene copolymer molecular chains have a size of less than 10 microns.
[0254] Table 2 lists the morphological characteristics of the modified spherulites of composition M4 in Example 8 and the spherulites of composition O6 in Comparative Example 11. The morphology and characteristics of the modified spherulites in Example 8 and Example 4 are essentially the same, differing only in: (1) the maximum diameter of the modified spherulites, (2) the composition of the bright area units, and (3) the greater proportion of the extinct dark area.
[0255] Based on the beneficial effects of the formed variant spherulites, the results of the crystallization peak temperature, half-crystal time, light transmittance, turbidity, tensile properties, bending properties, and impact properties of the ethylene polymer composition samples are shown in Table 3.
[0256] As previously mentioned, compared to EX1-1, the two components in EX4 have a higher matching rate. Table 3 shows that, compared to EX1-1, the highly matched composition M4, composed of EX4 and an ethylene copolymer, further increases crystallization temperature, shortens half-crystallization time, reduces turbidity, and improves mechanical properties, including tensile strength, tensile strain at break, and notched impact strength. This indicates that the difference ΔW between the peak positions of the characteristic absorption peaks of the NH bending and CN stretching coupling vibrations present in the infrared spectrum range of 1600-1400 for the two components of the composite organic modifier correlates with their enhanced crystallization, reduced turbidity, and improved mechanical properties in the ethylene copolymer. Therefore, to achieve an ethylene polymer composition with a higher crystallization temperature, shorter half-crystallization time, lower turbidity, and superior mechanical properties, the difference ΔW between the peak positions of the characteristic absorption peaks of the NH bending and CN stretching coupling vibrations present in the infrared spectrum range of 1600-1400 for Compound A and Compound B of the present invention is preferably no more than 15 wavenumbers, more preferably no more than 10 wavenumbers, and even more preferably no more than 5 wavenumbers, to further improve the matching rate between Compounds A and B. More beneficially, at the same dosage, the composite organic improver of the present invention not only has better effects, but also has lower costs than pure bisoxalyl diamide compounds.
[0257] Example 9
[0258] A composite organic improver of the present invention is composed of compound A and compound B, wherein compound A is N,N'-di(hexadecyl)oxalyl diamide of formula (I-2), and compound B is N-hexadecyl-N'-(2-((hexadecylamino)(oxo)acetyl)amino)ethyl)oxalyl diamide of formula (II-3), and compound A and compound B can induce ethylene polymer molecular chains to form variant spherulites through self-assembly heterogeneous nucleation, wherein the variant spherulites include a central bright region and an extinction dark region, wherein the extinction dark region surrounds the central bright region;
[0259]
[0260]
[0261] In this example, the mass ratio of compound A to compound B is 250:750, which is recorded as EX5.
[0262] In this embodiment, the characteristics of the composite organic improver are shown in Table 4, and the characteristics of the variant spherulites formed by inducing the formation of ethylene polymer molecular chains through self-assembly heterogeneous nucleation are shown in Example 11 of Table 5.
[0263] In this embodiment, the preparation method of the composite organic improver EX5 is prepared by referring to the preparation method 1 in Example 1, except that: the oxalic acid diester is 365.4 g (2.50 mol) of diethyl oxalate, the diamine is 60.1 g (1 mol) of ethylenediamine, and the monoamine is 965.8 g (4 mol) of hexadecylamine. Other process conditions remain unchanged. The obtained composite organic improver is recorded as EX5 with a yield of 92.5%.
[0264] Example 10
[0265] A composite organic improver of the present invention is composed of compound A and compound B, wherein compound A is a compound of formula (I-1) N,N'-diphenyloxalyldiamide and a compound of formula (I-3) N,N'-dihexyloxalyldiamide, and compound B is a compound of formula (II-1) N-phenyl-N'-(6-((oxy(phenylamino)acetyl)amino)hexyl)oxalyldiamide and a compound of formula (II-4) N-hexyl-N'-(6-((hexylamino)(oxy)acetyl)amino)hexyl)oxalyldiamide, wherein compound A and compound B can induce ethylene polymer molecular chains to form variant spherulites through self-assembly heterogeneous nucleation, wherein the variant spherulites include a central bright region and an extinction dark region, wherein the extinction dark region surrounds the central bright region;
[0266]
[0267] In this embodiment, the mass composition of compound A of formula (I-1), compound A of formula (I-3), compound B of formula (II-1), and compound B of formula (II-4) is 120:180:600:100, and the composite organic improver composed of them is recorded as EX6.
[0268] In this embodiment, the characteristics of the composite organic improver are shown in Table 4, and the characteristics of the variant spherulites formed by inducing the formation of ethylene polymer molecular chains through self-assembly heterogeneous nucleation are shown in Example 12 of Table 5.
[0269] In this embodiment, the preparation method of the composite organic improver EX6 is as follows:
[0270] S1. In a reactor equipped with a stirrer, a thermometer, a heating device, a dropping device and a condenser, 438.4 g (3 mol) of diethyl oxalate was added, and at room temperature (about 25° C.), a solution consisting of 116.2 g (1 mol) of hexamethylenediamine and 116 mL of ethanol was added dropwise to the diethyl oxalate to react to obtain a first reaction mixture;
[0271] S2, 900mL DMF was added to the first reaction mixture, heated until the mixture was dissolved, then a solution consisting of 202.4 grams (2mol) of hexylamine and 100mL of DMF was added and the mixture was refluxed at 60°C to 85°C. After completion of the reaction, a solution consisting of 279.4 grams (3mol) of aniline and 140mL of DMF was added and the mixture was refluxed again at 60°C to 85°C. After completion of the reaction, the obtained second reaction mixture was filtered, washed, and dried for refined separation to obtain a composite organic improver as a white powder and a block product, designated as EX6, with a yield of 91.5%.
[0272] Table 4 Composition and performance results of the composite organic improver in Examples 9 to 10
[0273]
[0274] It is explained that when the two components of the composite organic improver contain multiple compounds, the average value W of the amide II band peak position of compound A and compound B is taken respectively, and then the difference △W between compound A and compound B is calculated.
[0275] Example 11
[0276] The composite organic improver of the present invention is used as a polymer additive, specifically as an ethylene polymer additive. The preparation steps are basically the same as those in Example 4, except that the composite organic improver used is EX5, and an ethylene polymer composition is obtained, which is denoted as M5. The composition M5 is melted and crystallized to form a modified spherulite, such as Figure 11 The characteristics of the variant spherulites are shown in Table 5.
[0277] Example 12
[0278] The composite organic improver of the present invention is used as a polymer additive, specifically as an ethylene polymer additive. The preparation steps are basically the same as those in Example 4, except that the composite organic improver used is EX6, and an ethylene polymer composition is obtained, which is denoted as M6. The composition M6 is melted and crystallized to form a modified spherulite, such as Figure 12 The characteristics of the variant spherulites are shown in Table 5. Among them, the maximum diameter of the variant spherulites formed by heterogeneous nucleation is in the range of 50-220 μm, and the maximum diameter of the black cross extinction spherulites formed by homogeneous nucleation is in the range of 3-6 μm.
[0279] The characteristics of the modified spherulites of the ethylene polymer compositions M5 and M6 in Examples 11 and 12 are shown in Table 5. The polarizing microscope photos of the compositions M5 and M6 in Examples 11 and 12 are shown in Table 5. Figures 11-12 shown.
[0280] Table 5 Characteristics of variant spherulites of ethylene polymer compositions in Examples 11-12
[0281]
[0282] Based on the beneficial effects of the formed modified spherulites, the results of half-crystal time, light transmittance, turbidity, tensile properties and impact properties of each ethylene polymer composition are shown in Table 6.
[0283] Table 6 Performance results of ethylene polymer compositions of Examples 11 to 12
[0284]
[0285] The ethylene polymer compositions prepared in the above examples did not exhibit undesirable yellowing and precipitation after processing.
[0286] Table 6 further illustrates that the composite organic modifier of the present invention has the beneficial effects of promoting crystallization, shortening the molding cycle, reducing turbidity, and significantly increasing toughness without reducing rigidity in ethylene copolymers, while also having the advantages of low dosage and low cost. It also illustrates the important role of the difference ΔW between the amide II band peak positions between the components in the preference for compound A and compound B.
[0287] The above description is only a preferred embodiment of the present invention and does not constitute any formal limitation to the present invention. Although the present invention has been disclosed as above in terms of a preferred embodiment, it is not intended to limit the present invention. Any person skilled in the art can, without departing from the spirit and technical solution of the present invention, use the methods and technical contents disclosed above to make many possible changes and modifications to the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention, still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A composite organic improver, characterized in that: The composite organic improver is composed of compound A and compound B, wherein compound A is one or more monooxalyl diamide derivatives, and compound B is one or more bisoxalyl diamide derivatives, and the compound A and the compound B can induce the ethylene polymer molecular chain to form a variant spherulite through self-assembly heterogeneous nucleation, and the variant spherulite includes a central bright area and an extinction dark area, and the extinction dark area surrounds the central bright area; The structural formula of the monooxalyl diamide derivative is shown in formula (I): The structural formula of the bisoxalyl diamide derivative is shown in formula (II): R1, R2, R3, and R5 are independently one of a hydrocarbon group having 1 to 40 carbon atoms and a hydrocarbon group substituted with a hydroxyl group having 1 to 40 carbon atoms, and R4 is one of a hydrocarbon group having 1 to 40 carbon atoms.
2. The composite organic improver according to claim 1, characterized in that The composite organic improver has one or more of the following characteristics: (1) The difference ΔW between the peak positions of the characteristic absorption peaks of the NH bending and CN stretching coupling vibrations between the compound A and the compound B in the infrared spectrum within the range of 1600 to 1400 wavenumbers does not exceed 15 wavenumbers; (2) The composite organic improver has a characteristic absorption peak of NH stretching vibration in the wave number range of 3500-3100 in the infrared spectrum, and a characteristic absorption peak of carbonyl stretching vibration in the wave number range of 1700-1600; (3) The melting point range of the composite organic improver is 100°C to 370°C; (4) the composite organic improver is heated from 25° C. to a molten state and then cooled to 25° C. to form a fibrous structure; (5) The composite organic improver is characterized by two-stage thermal weight loss in the first-stage thermal weight loss temperature range of 100°C to 300°C and the second-stage thermal weight loss temperature range of 200°C to 450°C under thermogravimetric analysis, or multiple-stage thermal weight loss in the thermal weight loss temperature range of 100°C to 450°C.
3. The composite organic improver according to claim 2, characterized in that: In feature (1), the difference ΔW between the peak positions of the characteristic absorption peaks of NH bending and CN stretching coupling vibrations existing in the infrared spectrum range of 1600 to 1400 wavenumbers between the compound A and the compound B does not exceed 10 wavenumbers; And / or, in feature (3), the melting point range of the composite organic improver is 200°C to 320°C.
4. The composite organic improver according to claim 3, characterized in that In feature (1), the difference ΔW between the peak positions of the characteristic absorption peaks of NH bending and CN stretching coupling vibrations existing in the infrared spectrum range of 1600 to 1400 wavenumbers of the compound A and the compound B does not exceed 5 wavenumbers; And / or, in feature (3), the melting point range of the composite organic improver is 250°C to 300°C.
5. The composite organic improver according to any one of claims 1 to 4, characterized in that The mass ratio of the compound A to the compound B is 1-1000:1-1000.
6. The composite organic improver according to claim 5, characterized in that: The mass ratio of the compound A to the compound B is 1-100:1-100.
7. The composite organic improver according to any one of claims 1 to 4, characterized in that The variant spherulites have one or more of the following characteristics: (1) The overall morphology of the variant spherulites is spherical or quasi-spherical; (2) The maximum diameter of the mutant spherulites is 20 μm to 500 μm; (3) The central bright area is composed of one or more needle-shaped units, narrow dumbbell-shaped units or bundle-shaped units; (4) The central bright area is radial in shape as a whole; (5) The shape of the dark area includes one or more of a double semicircle, an oval, a circle, a jujube-shaped circle, and an oblate circle; (6) The area of the extinction dark zone accounts for 50% to 95% of the total area of the mutant spherulites.
8. The composite organic improver according to any one of claims 1 to 4, characterized in that Said R1, R2, R3, and R5 are independently selected from one or more of methyl, ethyl, propyl, butyl, isobutyl, pentyl, hexyl, heptyl, octyl, 2-ethylhexyl, nonyl, decyl, undecyl, dodecyl, tetradecyl, hexadecyl, octadecyl, cyclohexylmethyl, 1-cyclohexylethyl, 2-cyclohexylethyl, cyclohexyl, phenyl, benzyl, 4-methylbenzyl, 2-methylallyl, 2-hydroxyethyl, 3-hydroxypropyl, 2-hydroxybutyl, 4-hydroxybutyl, 5-hydroxypentyl, 6-hydroxyhexyl, 10-hydroxydecyl, 11-hydroxyundecyl, and 12-hydroxydodecyl; The R4 is selected from one or more of ethanediyl, propanediyl, butanediyl, pentanediyl, 2,2-dimethylpropane-1,3-diyl, hexanediyl, heptanediyl, octanediyl, decanediyl, dodecanediyl, cyclohexanediyl, methylbenzenediyl, dimethylbenzenediyl, benzenediyl, naphthalenediyl, biphenyldiyl, dimethylbiphenyl, diphenylmethanediyl, (1-methylethylidene)biphenyl-4,4'-diyl and 1,3,3-trimethylcyclohexylmethyl-5-yl.
9. A method for preparing a composite organic improver according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, adding oxalic acid diester to a reaction vessel, then adding diamine, and reacting at 0° C. to 40° C. to obtain a first reaction mixture; S2, adding solvent B to the first reaction mixture, heating until dissolved, then adding a monoamine, and performing a reflux reaction, wherein the monoamine is a hydrocarbon monoamine and / or an alcohol hydrocarbon monoamine, and is purified and separated to obtain a composite organic improver; The molar ratio of the oxalic acid diester, the diamine and the monoamine is m:1:(2m+n-2), 2.5≤m≤1000, and 0≤n≤10.
10. The method for preparing the composite organic improver according to claim 9, characterized in that: The preparation method has one or more of the following features (1) to (9): (1) In step S1, the oxalic acid diester includes one or more of dimethyl oxalate, diethyl oxalate, dipropyl oxalate, dibutyl oxalate and dioctyl oxalate; (2) In step S1, the diamine includes one or more of ethylenediamine, propylenediamine, butylenediamine, pentamethylenediamine, dimethylpropylenediamine, hexamethylenediamine, heptamethylenediamine, octanediamine, decanediamine, dodecanediamine, cyclohexanediamine, methylphenylenediamine, dimethylphenylenediamine, phenylenediamine, naphthalenediamine, benzyldiamine, dimethylbenzidine, 4,4'-diaminodiphenylmethane, 4,4'-(1-methylethylidene)dianiline, and 5-amino-1,3,3-trimethylcyclohexylamine; (3) In step S1, the diamine is first mixed with solvent A and then added to the reaction vessel, wherein the solvent A comprises one or more of a halogenated hydrocarbon having 1 to 5 carbon atoms, an alcohol having 1 to 40 carbon atoms, an amide having 1 to 6 carbon atoms, an N-substituted amide having 1 to 6 carbon atoms, and tetrahydrofuran; (4) In step S2, the hydrocarbon monoamine includes one or more of methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, heptylamine, octylamine, 2-ethylhexylamine, nonylamine, decylamine, undecylamine, dodecylamine, tetradecylamine, hexadecylamine, octadecylamine, behenyl primary amine, cyclohexylamine, cyclohexylmethylamine, 1-cyclohexylethylamine, 2-cyclohexylethylamine, aniline, benzylamine, 4-methylbenzylamine, and 2-methylallylamine; (5) In step S2, the alcohol-alkyl monoamine includes one or more of ethanolamine, propanolamine, 2-hydroxybutylamine, 4-hydroxybutylamine, 5-hydroxypentylamine, hexanolamine, hexanolamine, undecanolamine and dodecanolamine; (6) In step S2, the solvent B includes one or more of a halogenated hydrocarbon having 1 to 5 carbon atoms, an alcohol having 1 to 40 carbon atoms, an amide having 1 to 6 carbon atoms, an N-substituted amide having 1 to 6 carbon atoms, and tetrahydrofuran; (7) In step S2, the monoamine is first mixed with solvent E, which is the same as solvent B, and then added to the reaction vessel; (8) In step S2, the purification includes filtering, washing, and drying; (9) The diamine and the monoamine are added to the reaction vessel in the form of dropwise addition, flow addition or batch addition.
11. A method for preparing a composite organic improver according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Adding an oxalic acid diester and a monoamine into a reaction vessel and reacting at 0° C. to 85° C. to obtain a reaction intermediate, wherein the monoamine is a hydrocarbon monoamine and / or an alcohol hydrocarbon monoamine; S2, adding solvent D to the reaction intermediate, heating until dissolved, then adding diamine to carry out reflux reaction, and refining and separating after the reaction to obtain a composite organic improver; The molar ratio of the oxalic acid diester, the monoamine and the diamine is 1:p:(1-0.5p), and 1<p<2.
12. The method for preparing the composite organic improver according to claim 11, characterized in that: The preparation method has one or more of the following features (1) to (8): (1) In step S1, the oxalic acid diester includes one or more of dimethyl oxalate, diethyl oxalate, dipropyl oxalate, dibutyl oxalate and dioctyl oxalate; (2) In step S1, the hydrocarbon monoamine includes one or more of methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, heptylamine, octylamine, 2-ethylhexylamine, nonylamine, decylamine, undecylamine, dodecylamine, tetradecylamine, hexadecylamine, octadecylamine, behenyl primary amine, cyclohexylamine, cyclohexylmethylamine, 1-cyclohexylethylamine, 2-cyclohexylethylamine, aniline, benzylamine, 4-methylbenzylamine, and 2-methylallylamine; (3) In step S1, the alcohol-alkyl monoamine includes one or more of ethanolamine, propanolamine, 2-hydroxybutylamine, 4-hydroxybutylamine, 5-hydroxypentylamine, hexanolamine, hexanolamine, undecanolamine and dodecanolamine; (4) In step S1, the monoamine is first mixed with a solvent C and then added to the reaction vessel, wherein the solvent C comprises one or more of a halogenated hydrocarbon having 1 to 5 carbon atoms, an alcohol having 1 to 40 carbon atoms, an amide having 1 to 6 carbon atoms, an N-substituted amide having 1 to 6 carbon atoms, tetrahydrofuran, acetonitrile, and an aromatic hydrocarbon; (5) In step S2, the diamine includes one or more of ethylenediamine, propylenediamine, butylenediamine, pentamethylenediamine, dimethylpropylenediamine, hexamethylenediamine, heptamethylenediamine, octanediamine, decanediamine, dodecanediamine, cyclohexanediamine, methylphenylenediamine, dimethylphenylenediamine, phenylenediamine, naphthalenediamine, benzyldiamine, dimethylbenzidine, 4,4'-diaminodiphenylmethane, 4,4'-(1-methylethylidene)dianiline, and 5-amino-1,3,3-trimethylcyclohexylamine; (6) In step S2, the solvent D includes one or more of a halogenated hydrocarbon having 1 to 5 carbon atoms, an alcohol having 1 to 40 carbon atoms, an amide having 1 to 6 carbon atoms, an N-substituted amide having 1 to 6 carbon atoms, tetrahydrofuran, acetonitrile, and an aromatic hydrocarbon; (7) In step S2, the diamine is first mixed with solvent F, which is the same as solvent D, and then added to the reaction vessel; (8) The refining includes filtering, washing, and drying; (9) The monoamine and the diamine are added to the reaction vessel in the form of dropwise addition, flow addition or batch addition.
13. Use of the composite organic improver according to any one of claims 1 to 8 or the composite organic improver prepared by the preparation method according to any one of claims 9 to 12 as a polymer additive.
14. The use according to claim 13, characterized in that The polymer is an ethylene polymer.
